Contribution of Murabahah Financing and Liquidity Towards the Profitability of BMT UGT Nusantara Capem Jajag - Dea Amelia Fitria; Nur Anim Jauhariyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyse the influence of financing Murabahah and liquidity to the profitability of BMT UGT Nusantara Capem Jajag Banyuwangi. Research methods use quantitative approach with analysing secondary data report on finance from 46 months in 2020-2023, with independent consists of from financing Murabahah and liquidity, whereas dependent is profitability. Data analysis using multiple linear regression with SPSS software. The results of the analysis show that the variable independently influential positive and significant to profitability. The t-test shows that financing murabaha has t-count of 8.189 more big from t table value with significance 0.000 <0.05, and liquidity has t-count of 2.078 more big from t table value with mark significance 0.044 < 0.05, both variable in a way partial show mark significant with simultaneous test results significant. The magnitude mark coefficient determination (R²) of 0.609 means 60.9% of the variation in profitability at BMT UGT Nusantara Jajag Gambiran Banyuwangi can be explained by financing murabahah and liquidity.